A practical method to improve preoxygenation: Using the APL valve (Annals of Medical Research, 2021)
Aim: After induction of anesthesia hypoxemia may rapidly develop due to hypoventilation, apnea and decrease in functional residual capacity. Thus, preoxygenation should be administered to every patient before anesthesia induction since airway management may unexpectedly be difficult. Applying positive airway pressure is reported to improve preoxygenation. In this study, we aimed to investigate the effect of applying positive pressure via the adjustable pressure limiting valve (APL) on preoxygenation.Material and Methods: 40 patients aged from 18 to 80 years to be operated under general anesthesia were included in this prospective randomized controlled study. The patients were randomly divided into two groups and preoxygenation was administered with anesthesia facemask in the supine position using two different techniques. In both techniques, the anesthesia circuit was flushed with O2 flush for 30 seconds and then preoxygenation was performed with 100% oxygen and 12 L/min of fresh gas flow for 3 min in spontaneous breathing. In Group APL the APL valve was set at 5 cmH2O pressure position. In Group SB, the APL valve was set at open (spontaneous) position. Results: The percentage of patients with an FeO2 of ≥ 90% at 3rd min was higher in Group APL than in Group SB (75% vs 40%, p=0.006). The mean FeO2 value at 3rd min was statistically significantly higher in Group APL (89.6 vs 88.2, p=0.001). The degree of the difficulty of the technique was reported to be higher in Group APL. Conclusion: In conclusion, we have shown that applying 5 cmH2O positive pressure by APL valve improved preoxygenation compared with spontaneous breathing.